Virtual Path Navigation using Two Rotary Encoders - Lee, Jia Sheng; Chia, Kim Seng (International Journal of Electrical Engineering and Applied Sciences (IJEEAS), 2019)
The aim of this project is to evaluate the feasibility of the use of two rotary encoders in navigating an automated guided vehicle (AGV) in more complex virtual paths that include 90 and 180 degree turning from one to another desired positions. The proposed AGV was remotely controlled using a Bluetooth in a smart phone. The proposed AGV consisted of a microcontroller,two rotary encoders, an ultrasonic sensor, and a Bluetooth. The overshoot and systematic error was minimized using experiment data when the AGV was turning. The readings of the rotary encoders were mapped to the actual travel distance via calibration experiments so that the AGV can be redesigned to travel in different desired path without repeating the calibration experiments.Findings indicate that the proposed navigation method can navigate the AGV from one location to another location without installing any physical path or track.